Time Dynamics and Incomplete Information in the Private Provision of Public Goods - Gradstein, Mark (Journal of Political Economy, 1992)
In this paper a dynamic model of the provision of a public good with incomplete information is developed. For a finite population, in addition to the standard underprovision type of results, inefficiency occurs because of a delay in contributions. For an infinite population, although delay may disappear, underprovision remains so that equilibrium is still inefficient. Policy implications of these results are described, emphasis being put on possible government intervention with incomplete information.